Lactobacillus acidophilus Endocarditis Complicated by Pauci-Immune Necrotizing Glomerulonephritis - Vivian O. Chukwurah; Comfort Takang; Chinelo Uche; David B. Thomas; Waguih El Masry; Hakan R. Toka (Case Reports in Medicine)
Infective endocarditis (IE) is more common in patients with predisposing cardiac lesions and has many potential complications, including stroke and arterial thromboembolisms. Renal manifestations have an estimated prevalence of ∼20%. Rapidly progressive glomerulonephritis (RPGN) is a nephrological emergency manifested by autoimmune-mediated progressive loss of renal function over a relatively short period of time. Here, we report the case of a 60-year-old Caucasian male, who presented with speech impairment and was found to have multiple embolic strokes caused by aortic valve IE. His renal function declined rapidly, and his urine sediment featured hematuria and proteinuria. ANCA titer was negative by immunofluorescence (IF); however, the PR3 antibody was elevated. The renal biopsy revealed pauci-immune focally necrotizing glomerulonephritis with the presence of ∼25% cellular crescents. He was initially treated with plasmapheresis and pulse dose steroids. Hemodialysis was initiated for uremic symptoms. After four weeks of antibiotic therapy and with blood cultures remaining negative, he was treated with rituximab. Two months after discharge, his renal function showed improvement, and hemodialysis was discontinued. This case highlights several complications associated with lactobacillus endocarditis including RPGN.